A Christian Perspective on Personhood Formation: Theological Premises in Dialogue with Theoretical Frameworks. Issue 2 (3rd May 2020) - de Muynck, Bram; Visser-Vogel, Elsbeth
Abstract: Though personhood formation is often perceived as an important aim of Christian education, there is little clarity about how the concept can be understood from a Christian perspective. Furthermore, teachers lack the tools to nourish the development of students' personhood. In this article, we develop a framework that aims to fill these gaps. The framework is built in three hermeneutical steps. We first present five theological premises that inform our perspective. Second, we discuss six theories that are frequently used in academic work and educational policy. Finally, in the discussion section, we summarize conflicting and cohering aspects, and map a number of practical guidelines based on the conclusions of the previous two steps. We conclude that personhood formation cannot be reduced to a certain part of the curriculum, but that it has to be an integral part of the pedagogy.